Etymological Memory of a Word in Designating Sociocultural Stereotype - Lyubimova, Svitlana (Lesya Ukrainka Eastern European National University, 2017)
The article presents the semantic history of the word flapper that denotes social stereotype of American culture. Being a multifaceted phenomenon of semantic cognition, a sociocultural stereotype presents a condensed and coded information that develops on the background of a cultural context. The semantic analysis from diachronic perspective sets up a correspondence of Latin origin of the word flapper with Indo-European stem that produced a number of words in Germanic languages. The cognate words of related languages reveal conformity of negative connotations determined by attitude to human weakness in different forms of its manifestations. This presumes historically determined negative connotation of the word flapper. The initial designation was motivated by kinetic characteristic of the object – a vertical movement. The meaning “a young and daring American girl of the 1920s” of the word flapper was semantically motivated. As it was stated, at the moment of designation, youth and immaturity of a girl were conceived of a fledgling image, that traditionally symbolizes inexperience of a youngster. This zoomorphic metaphor acts as the source of categorization of a cultural and social phenomenon “Flapper”. У статті презентовано семантичний аналіз слова flapper, яке позначає соціокультурний стереотип, що появився в 20-х роках 20-го століття в Америці. Стереотип є концентрованою й абстрагованою формою семантичної пам’яті народу, в якій збережено етнічно і культурно маркований образ. Упродовж етимологічного аналізу було доведено, що основі слова flapper, яка має індоєвропейське походження, відповідає певна кількість слів споріднених мов, негативна конотативна забарвленість яких дає можливість визнати історичну детермінованість конотації слова flapper. Позначення первинного образу було мотивовано кінетичною характеристикою образу, тоді як значення «молода смілива дівчина в Америці 20-х років 20-го століття» слова flapper було семантично зумовлено. Сприйняття молодості та незрілості відбувалось на метафоричній основі образу пташеня, що асоціювався з несталістю моральних принципів молодих дівчат. Зооморфна метафора діє як джерело категоризації соціально-культурної інформації, що сприймалась критично. Первинний образ, який зумовив появу нового значення, визначив прагматичний потенціал слова, що позначає соціально-культурне явище.
Keywords: sociocultural stereotype; initial designation; zoomorphic metaphor; pragmatic presupposition; connotation; соціокультурний стереотип; первинна номінація; зооморфна метафора; прагматична пресупозиція; конотація